Pallidoreticular Damage in Acute Carbon Monoxide Poisoning: Diffusion-Weighted MR Imaging Findings - Kinoshita, Toshibumi; Sugihara, Shuji; Matsusue, Eiji; Fujii, Shinya; Ametani, Motoki; Ogawa, Toshihide (American Journal of Neuroradiology, 2005)
Summary: We describe a case of carbon monoxide poisoning that led to pallidoreticular damage and delayed leukoencephalopathy. Serial diffusion-weighted MR imaging was performed. A restricted water diffusion pattern was demonstrated in the globus pallidus and substantia nigra in the early stage. Diffusion-weighted imaging is useful for early identification of the effects of acute carbon monoxide poisoning.